PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN MOTIVASI BERPRESTASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN AKUNTANSI FPEB UNIVERSITAS PENDIDIKAN INDONESIA - Alif Fauzia Restiadi; Kurjono Kurjono; Yana Setiawan (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2021)
This reseach present the lack of entrepreneurial intention in student, so the impact that has caused is an increase in the number or unemployment rate in Indonesia. The aims of this research are to describe the effect of entrepreneurial learning, achievement motivation and entrepreneurship intention, and also the effect of effect of entrepreneurial learning, achievement motivation on entrepreneurship intention of Accounting Education FPEB major student period 2016, 2017 and 2018 at Indonesia University Of Education (Universitas Pendidikan Indonesia). Using Theory Behavior Planed, this research use descriptive and verification methods. The population of this study consist 254 Accounting Education, there are student class 2016, 2017, and 2018, with research sample of 155 Students. The research use random sampling method. The instrument validity was assessed by product moment correlation and the reliability by cronbach’s alpha, using questionnares as a data collection technic. The classic assumption test includes the normality test, the linearity test, the multicollinearity test, and the heteroscedasticity test. All data calculation is done by using Microsoft Statistical Product and Service Solution (SPSS) v25 and Microsoft excel 2016. From the calculation results of the t test on each variable entrepreneurial learning and, achievement motivation the result of t-test shows tstatistic>ttabel , i.e. variable entrepreneurial learning obtained by tstatistic: 4.297 > ttabel : 1.97569 and variable achievement motivational obtained by tstatistic: 4.572 > ttabel : 1.97569. The result of study showed that entrepreneurial learning and achievement motivation has a positive effect on entrepreneurship intention of Students Accounting Education FPEB period 2015, 2016 and 2017 at Indonesia University of Education (Universitas Pendidikan Indonesia). The suggestions that can be given from this research are to increase the mindset, knowledge, skills and participation in learning and dare to start a business because it’s important in increasing interest in entrepreneurship.